ANALYTICAL RESULTS OF RADIATION HYGIENIC CERTIFICATION OF TERRITORIES FROM CONSTITUENT ENTITIES OF THE RUSSIAN FEDERATION FOR 2008 AND MEASURES FOR ITS FURTHER IMPROVEMENT - . Роспотребнадзор (Радиационная гигиена)
.